Research-Based Learning to Foster Students' Creative Thinking and Independence - Puput Suriyah; Stevanus Budi Waluya; Dwijanto Dwijanto; Isnaini Rosyida (International Conference on Science, Education, and Technology, 2022)
The purpose of this study is to describe a research-based learning model to foster students' creative thinking skills and independence. A Systematic Literature Review (SLR) is used as a method of analyzing of various articles and literature obtained by searching for data sources. The results of the analysis from these various sources are translated detailed review. Creative thinking skills in mathematics are needed to create (formulate), complete, and complete a model or problem-solving plan. The ability to think creatively needs to be developed as the main provision to face life. The importance of independent learning in schema thinking helps build components of a schema that are connected in a network of creative thinking abilities. To develop these two goals, namely the ability to think creatively mathematically and independent learning, it is necessary to pursue a learning activity that further explores the ability of students to solve problems creatively, and in the process helps to develop independent learning. The learning model that leads to these benefits is Research-Based Learning.